PROBLEMS OF DEVELOPMENT OF NEW PEDAGOGICAL TECHNOLOGIES OF TRAINING OF TEACHERS OF PROFESSIONAL EDUCATION AND THEIR INTRODUCTION INTO THE EDUCATIONAL AND EDUCATIONAL PROCESS (Academicia Globe: Inderscience Research, 2022)
In the conditions of independence, the activities of the educational institutions of the Republic of Uzbekistan are carried out by a number of leading organizations on the introduction of new pedagogical technologies into the process. In particular, the activities carried out by organizations such as the International Soros Foundation (Open Institute), AXELS, IREX, JISA are of particular importance with its effectiveness. Over the past five years, innovative (pedagogical technology) centers have been established under a number of leading higher educational institutions of the Republic on the basis of support and encouragement of the organizations named above.